Professionalism of Islamic spiritual guide - Susana Aditiya Wangsanata; Widodo Supriyono; Ali Murtadho (Journal of Advanced Guidance and Counseling, 2020)
Purpose - The aim of this research was to recognize radically (deeply) the professionalism of Islamic spiritual guides.Method - This research used descriptive qualitative with the determination of informants using the model of snowball. The data analysis in this study used Creswell's theory of analysis ranging from data reduction, display, and to conclutions.Result - The results of this study indicate that a professional Islamic spiritual guide needs to meet three indicators in order to carry out counseling process optimally. The indicators of professionalism are relevant educational qualifications, expertise or qualified credibility, and finally the presence of payment commensurate with the quality of work. Meanwhile, the professionalism of Islamic spiritual guidance services is to pay attention to the time and material given to counselees so that they can display or provide Islamic spiritual guidance services professionally.Implications - The implication of this research is to improve performance professionally by absorbing the experts or specialists in the field of Islamic spiritual guidance.Originality - The originality of this study is that it is the first research model to apply the correlation research method with the LESKAP pattern. Tujuan - Penelitian ini bertujuan untuk mengetahui secara radikal (mendalam) profesionalisme pembimbing spiritual Islam.Metode - Penelitian ini menggunakan deskriptif kualitatif dengan penentuan informan menggunakan model snowball. Analisis data dalam penelitian ini menggunakan teori analisis Creswell mulai dari reduksi data, penyajian, dan penarikan kesimpulan.Hasil - Hasil penelitian ini menunjukkan bahwa seorang pembimbing spiritual Islam profesional perlu memenuhi tiga indikator agar dapat melaksanakan proses penyuluhan secara optimal. Indikator profesionalisme diantaranya, kualifikasi pendidikan yang relevan, keahlian atau kredibilitas yang mumpuni, dan terakhir adanya perhatian yang sepadan dengan kualitas pekerjaan. Sedangkan profesionalisme layanan bimbingan spiritual Islam adalah dengan memperhatikan waktu dan materi yang diberikan kepada konselor sehingga dapat menampilkan atau memberikan layanan bimbingan spiritual Islam secara profesional.Implikasi - Implikasi dari penelitian ini adalah untuk memberikan saran dalam hal meningkatkan kinerja secara profesional dengan menyerap tenaga ahli atau spesialis di bidang pembinaan spiritual Islam.Originalitas - Keaslian penelitian ini adalah model penelitian yang pertama kali menerapkan metode penelitian korelasi dengan pola LESKAP.